Answer:
the answer is 23 on edguniity
Step-by-step explanation:
The value of x is -2
Step-by-step explanation:
Given that
6 (2x + 3) - 3(x - 2) = 6
Expand the bracket
6 (2x + 3) - 3(x - 2) = 6
12x + 18 - 3x + 6 = 6
Collect like terms
12x - 3x = 6 - 6 - 18
9x = -18
Divide through by 9
9x / 9 = -18 / 9
x = -2
Therefore, the value of x is -2
Learn more about inequality here : brainly.com/question/20252161
If you would like to evaluate 6 * [5 * (3 - 9) - 1] + 2 / 7 * (8 - 2) + 4, you can calculate this using the following steps:
6 * [5 * (3 - 9) - 1] + 2 / 7 * (8 - 2) + 4 = 6 * [5 * (-6) - 1] + 2/7 * 6 + 4 = 6 * [- 30 - 1] + 12/7 + 4 = 6 * [- 31] + 12/7 + 4 = - 186 + 12/7 + 4 = - 182 + 12/7 = - 1274/7 + 12/7 = - 1262/7
The correct result would be - 1262/7.
Answer:
Yes
Step-by-step explanation:
14/18 equals 7/9
Dividing by two on the first ratio makes:
7/9 equals 7/9
Yes
No
Yes
No
This is because in order to be addition property of equality they have to add/ subtract by the same exact amount on both sides.